Wokół założeń metody wyjaśniania natury transformacji - Kramarek, Maciej (Explaining the nature of transformation process – the dispute on cognitive assumptions, 2006)
The author tries to prove that conclusions which are formulated as a result of systemic economic analysis are ever questionable. The discussion on their justification taking place on the level of general philosophy of market economic system and economic policy usually results in going away from microeconomic foundations of objectives and effectiveness of economic policy. On the contrary, an analysis which reveals causal relationships in the economy leads to conclusions which are microeconomically relevant. Such conclusions also enable researchers to formulate some hardly question nable implications concerning the way in which the economic system as a whole is organized. This interpretation of systemic changes in transitional economies may be subject to the accusation that it does not allow for drawing macroeconomic conclusions because of marginal bearing of single economic phenomena upon the entire economic life. Regardless of a highly disputable nature of this accusation from the methodological point of view, it is unquestionable that the more causes of phenomena taking place within the transformation process we are able to explore, the more scientifically justified our predictions on the course of transformation process and the more plausible their acceptance by representatives of various streams in the economic thought.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12), 2006, nr 1122, s. 153-166